FAKTOR-FAKTOR PENYEBAB KEKAMBUHAN PADA PASIEN SKIZOFRENIA DI POLIKLINIK JIWA RSUD H. ANDI SULTHAN DG. RADJA KABUPATEN BULUKUMBA - Edison Siringoringo; Haerati (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2019)
Schizophrenia is a person who has a psychiatric problem, or a disturbed personality such as thoughts, feelings, hearing, emotions, language, delusions, and behavior that is not in accordance with other normal humans. Reason If the disease is not treated it will cause adverse effects and endanger the patient, family, and society because they can behave like a tantrum, act as they please, destroying goods or patients will hurt others even themselves. Factors studied were family support, age, and adherence to taking medication. The purpose of this study was to determine the factors that cause recurrence in schizophrenic patients in the Catholic Cl Schizophrenia is a person who has a psychiatric problem, or a disturbed personality such as thoughts, feelings, hearing, emotions, language, delusions, and behavior that is not in accordance with other normal humans. Reason If the disease is not treated it will cause adverse effects and endanger the patient, family, and society because they can behave like a tantrum, act as they please, destroying goods or patients will hurt others even themselves. Factors studied were family support, age, and adherence to taking medication. The purpose of this study was to determine the factors that cause recurrence in schizophrenic patients in the Catholic Clinic of H.Andi Sulthan Hospital Dg. Radja Regency of Bulukumba. The research design uses analytical design with cross sectional approach. The population in the study were all schizophrenic patients who had schizophrenia accompanied by a family for 1 month at the mental clinic of H. Andi Sulthan Hospital Dg. Radja Bulukumba obtained data from January-March as many as 135 people, with sampling techniques using non-probability sampling. The number of samples in this study were 57 respondents. Data obtained through questionnaires made by researchers to respondents. Data analysis using Fisher's alternative Chis-quare test and Kolmogorov-Smirnov test, with a significance level of α = 0.05. The results of data analysis showed age variables p = 0.032, family support p = 0.005, and medication adherence variables p = 0.025. Conclusion that there is a relationship between age, family support, medication adherence to the recurrence of schizophrenia in the mental clinic of H. Andi Sulthan Hospital Dg. Radja in Bulukumba District in 2018. Suggestion expected This research can be used as additional knowledge to reduce the frequency of recurrence of schizophrenic patients. inic of H.Andi Sulthan Hospital Dg. Radja Regency of Bulukumba. The research design uses analytical design with cross sectional approach. The population in the study were all schizophrenic patients who had schizophrenia accompanied by a family for 1 month at the mental clinic of H. Andi Sulthan Hospital Dg. Radja Bulukumba obtained data from January-March as many as 135 people, with sampling techniques using non-probability sampling. The number of samples in this study were 57 respondents. Data obtained through questionnaires made by researchers to respondents. Data analysis using Fisher's alternative Chis-quare test and Kolmogorov-Smirnov test, with a significance level of α = 0.05. The results of data analysis showed age variables p = 0.032, family support p = 0.005, and medication adherence variables p = 0.025. Conclusion that there is a relationship between age, family support, medication adherence to the recurrence of schizophrenia in the mental clinic of H. Andi Sulthan Hospital Dg. Radja in Bulukumba District in 2018. Suggestion expected This research can be used as additional knowledge to reduce the frequency of recurrence of schizophrenic patients.